PENELAAHAN BUKU TEKS PELAJARAN KURIKULUM 2013 DITINJAU DARI ASPEK KELAYAKAN ISI, PENYAJIAN, BAHASA, DAN KEGRAFIKAAN - Suratni Suratni; Jimmy Paat (Politeknik Negeri Media Kreatif, 2014)
The purpose of this research is to examine the results of the review of the Independent Reviewer Team. The researcher uses a qualitative descriptive method to describe valuations of the reviewer. Furthermore, she reduces the data and sets 18 textbooks for this research data (23,68%). Overall, the aspectsof the feasibility of textbooks in Curriculum 2013 is divided into two categories, namely 'quite decent ' and ' worthy '. However, to make it a textbook in use nationally, aspects of the content, the presentation, the language, and the printing quality of the book have to be repaired, fitted, and maximized again.